Extremely efficient crystallization of HKUST-1 and Keggin-loaded related phases through the epoxide route - Oestreicher, Víctor Santiago Jesús (2017)
Highly crystalline HKUST-1 and COK-16-like phases were obtained based on a mild in situ alkalinization one-pot epoxide driven method. A slurry composed of finely ground trimesic acid, H3BTC, dispersed in a CuCl2 aqueous solution quantitatively developed well crystallized HKUST-1 after the addition of propylene oxide. The use of solid H3BTC ensures a low concentration of free linker, favoring crystalline growth over the precipitation of amorphous or metastable impurities. An extreme space-time yield of 2.1 × 105 kg m-3 day-1 was reached, with no linker excess and minimum use of solvent. The method was equally efficient in the achievement of pure NENU/COK-16 phases, containing [PW12O40]3-, [PMo12O40]3- and [SiMo12O40]4- polyoxometalates.